The reflection of strategic knowledge management on an improvement of excellent performance: A survey study at the Institution of Industrial Development and Research- the Ministry of Iraqi Industry (IDRMII) - eubayd, fatima alaa aldiyn; Mohammed, Atheer Abdullah (Journal of Economics and Administrative Sciences, 2020)
The current study aims to investigate the effect of strategic knowledge management practices on an excellent performance at the Institution of Industrial Development and Research- the Ministry of Iraqi Industry (IDRMII). The present research is designed according to the descriptive method. To achieve the mentioned research objective, the researchers used the questionnaire as the main data collection tool. The research sample was 150 managers who are working at the top and middle management levels. To analyses the data gathered and reaching the results, several statistical techniques were used within AMOS.V25, SPSS.V21Software, This study reached a set of results, the most important of which is the existence of a positive correlation and effect relationships between strategic knowledge management practices and the indicators of excellent performance at the researched organization. This result leads to the key conclusion that IDRMII invests knowledge mainly in improving its excellent performance, as well as exploring knowledge and creating the knowledge and its participation in the overall processes aimed at enhancing this performance in a synergistic manner. The findings also show the interest of IDRMII in its excellent performance and instinct to employ strategic knowledge management; more especially, when IDRMII invests knowledge after exploring it, makes strategic meaning about it, and shares knowledge in that interest. The focus on the one institution which is represented by IDRMII, and within one workplace environment (the industrial environment) is considered the main limitations of this study. This is because it is difficult to generalize the results to other sectors and environments. The scientific implications of the research were represented by investigating the nature of the influence and correlation relationships between strategic knowledge management practices and excellent performance, It is represented by the necessity of increasing awareness of senior administrative leaders and decision-makers in industrial organizations towards the importance of administrative concepts which are highlighted on the current study. More specifically, this study sheds light the vital role of strategic knowledge management practices in achieving the highest excellent levels of performance for industrial organizations, The research was drawn from a master thesis that has not discussed yet, This research adds a modest value to the Iraqi academic library in the field of knowledge and strategic management through providing a conceptual and practical model of affecting strategic knowledge management practices on excellent performance, Research paper.